2016
DOI: 10.1117/12.2222064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oil spill detection sensors in low-light environments

Abstract: Although advances have been made in oil spill remote detection, many electro-optic sensors do not provide real-time images, do not work well under degraded visual environments, nor provide a measure of extreme oil thickness in marine environments. A joint program now exists between BSEE and NVESD that addresses these capability gaps in remote sensing of oil spills. Laboratory experiments, calibration techniques, and field tests were performed at Fort Belvoir, Virginia; Santa Barbara, California; and the Ohmset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the Short Wave Infrared (SWIR) band (1000-1700 nm), crude oil has a different reflectance spectrum when compared to water [24]. The use in low light conditions is tested in [25], and it has been proven to be successful. The high cost and the limited commercial availability is the downside of this solution.…”
Section: Literaturementioning
confidence: 99%
“…In the Short Wave Infrared (SWIR) band (1000-1700 nm), crude oil has a different reflectance spectrum when compared to water [24]. The use in low light conditions is tested in [25], and it has been proven to be successful. The high cost and the limited commercial availability is the downside of this solution.…”
Section: Literaturementioning
confidence: 99%
“…The reflectivity measurements presumed that reflectivity was greatest for the thickest oils, however other studies show this is not the case. Allik et al measured the reflectivities of two oils and one emulsion, and the results showed that reflectivities varied [44]. The Alaska North Slope (ANS) crude showed lesser reflectivity than its emulsions.…”
Section: Near-infrared Reflectancementioning
confidence: 99%
“…Allik et al carried out a reflectivity study of oils and emulsions of various thicknesses over the range of 300 to 2300 nm [44]. It was noted that the spectra were very similar in the visible range, but the emulsions had higher reflectivity in the spectral region of 900 to 2300 nm (SWIR).…”
Section: Spectral Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…When discussing the challenges of measuring oil slick thickness, Fingas could not find consistent spectral signatures to gauge oil slick thickness [1]. In contrast, the long wave infrared (LWIR) atmospheric window has been used for the identification of millimeter oil spills [8][9][10][11][12]. Oil spill detection with uncooled, inexpensive microbolometers is well established and relies on capturing thermal radiation, not filtered spectra.…”
Section: Introductionmentioning
confidence: 99%